2022
DOI: 10.3390/ijerph19073995
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Knowledge, Attitudes and Practices amongst Women in Qatar

Abstract: This cross-sectional study examines knowledge, attitudes, and practices surrounding breast cancer awareness and screening among women residents in Qatar. Females, >18 years old, registered with the Primary Health Care Corporation were invited to complete an Arabic or English online survey using a modified version of the Breast Cancer Awareness Module. Of the 9008 participants, 69% report awareness of breast cancer warning signs, but the results did not substantiate these claims. There remains a disconnect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This study indicates that breast cancer is most prevalent among women aged 40-49 (48%), followed by those aged 50-59 (25%), and only 10% in the ≥60 age group. The findings align with previous research in Iraq and Qatar [19,20,21], where the highest incidence was observed in the 40-49 age range. However, contrasting results were noted in Europe, where only 25% of cases were >50 years old [22].…”
Section: Discussionsupporting
confidence: 91%
“…This study indicates that breast cancer is most prevalent among women aged 40-49 (48%), followed by those aged 50-59 (25%), and only 10% in the ≥60 age group. The findings align with previous research in Iraq and Qatar [19,20,21], where the highest incidence was observed in the 40-49 age range. However, contrasting results were noted in Europe, where only 25% of cases were >50 years old [22].…”
Section: Discussionsupporting
confidence: 91%
“…Several countries have screening programs for breast cancer, with letters sent to women reaching a certain age inviting them to participate, followed by letters at regular intervals to remind them to participate (16,19). The KAP toward breast cancer screening varies widely among countries with different characteristics, customs, and healthcare systems (22)(23)(24)(25). A study in Saudi Arabia showed that most women had poor knowledge of breast cancer screening and screening methods, and social media was their main source of information (22).…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia offers a free breast cancer screening program to all women above age 40 (31), and access to breast cancer screening should not be an impediment to knowledge acquisition. In Jordan, most women had adequate participation in breast cancer screening (25), despite the fact that Qatar has a program inviting women ages 45-69 to undergo breast cancer screening every 3 years (32). Healthcare professionals are first-line sources of reliable health-related knowledge for many individuals (33,34), highlighting the need for proper training and knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation